Rasio Senyawa Enansiomer sesamin di dalam kulit batang Pentaspadon motleyi (Anacardiaceae) - CHINAMI KITAMURA; PARTOMUAN SIMANJUNTAK; KAZUYOSHI KAWAZOE; SHOJI MAEHARA; KOZUYOSHI OHASHI; HIROTAKA SHIBUYA (Fakultas Farmasi Universitas Pancasila, 2011)
The barks of Pentaspadon motleyi Hook. f. (Anacardiaceae) were collected from the Poso district in Central Sulawesi, Indonesia, in 1992 which it has been used traditionally as a remedy for malaria and tuberculosis in the local area. It was found that a mixture of (+)-sesamin (1) and (-)-sesamin (2) in a ratio of 100:86 were present together with lupeol in the bark of Pentaspadon motleyi. This was the first evidence of sesamin being isolated in almost equivalent amounts of (+)- and (-)-forms from a single plant species, and indicates that the biosynthetic pathway of sesamin in the plant is not enantioselective or fuzzy.